Wezwanie : na podstawie art. 72 Ustawy z dnia 22 września 1946 r. [...] / St. Zrałek. - Zrałek, Stanisław (1907-1954) (Wojewoda Gdański, 1946)
Wezwanie do właścicieli pojazdów mechanicznych z 16.11.1946 r.